Arterio-venous and lymphatic malformation mimicking acute appendicitis in a patient. Case report and review of literature - Majeed, Talal; Allan, Jennifer; Magee, Conor; Wilson, Jeremy (Indian Journal of Case Reports, 2019)
Arteriovenous and lymphatic malformations are a common phenomenon and can present in various clinical forms. They rarely present as a cause of acute abdomen, and in the literature, there are only a few cases where intra-abdominal arteriovenous malformation (AVM) presented as acute appendicitis in the adult population. Most of the cases are diagnosed post-operatively on histology but the previous reporting in the literature has made it possible for the radiologists to look for these anomalies and consider them as a probable cause of acute abdomen when no other obvious cause is found. We are presenting an interesting case of congenital vascular malformation mimicking acute appendicitis in a young female. She had a previous history of complications related to AVM and her complicated urological history was initially focussed causing a delay in referral to surgeons and imaging which lead to the finaldiagnosis.